Fleeing Domestic Violence from a “Safe” Country?: Refugee Determination for Mexican Asylum-Seekers in Canada - Bhuyan, Rupaleem; Vargas, Adriana; Píntín-Perez, Margarita (Refuge: Canada's Journal on Refugees, 2016)
This article presents a mixed-methods study of domestic-violence-related claims for Mexican asylum-seekers in Canada. Although refugee claims that indicate domestic violence are slightly more likely to be approved, the majority of Mexicans seeking protection from domestic violence are denied because they are unable to demonstrate the lack of state protection. Our findings illustrate that Immigration and Refugee Board members’ assessment of a claimant’s credibility, internal flight alternatives, and the availability of state protection pivot on their perception of Mexico as a “democratic” or “safe” nation. We discuss how cursory attention to the social context of gendered violence in Mexico leaves Mexicans with few legal options for humanitarian migration.